Compression-induced crimping of boron nanotubes from borophenes: a DFT study - Qin, Xueqin; Liu, Jia; Mu, Yuewen; Li, Si-Dian (Physical chemistry chemical physics : PCCP, 2022)
Several borophenes have been prepared successfully, but the synthesis of boron nanotubes is still very difficult. Our results suggest that the high flexibility of borophene in combination with van der Waals interactions makes it possible to coil boron nanotubes from rippled borophenes, which is confirmed by ab initio molecular dynamics simulations. The plane structures transform into rippled structures almost without any barrier under very small compression and weak perturbations like molecular adsorption. The compression energies of the rippled structures increase linearly and slowly with the increase of the compression. This suggests how the geometry of the borophene evolves with compression. Based on the evaluation of the free energy of hydrogen adsorption, a stronger compression suggests the improved hydrogen evolution performance of the borophene and even makes it better than Pt catalysts. Meanwhile, good hydrogen evolution performance is also suggested for boron nanotubes. Our results suggest a novel preparation method for boron nanotubes from borophenes and a possible way to improve their hydrogen evolution performance. High flexibility of borophene and vdW interactions make it possible to coil boron nanotubes from rippled borophenes, and the compressions improve the HER performance of borophenes.